STEADY AND UNSTEADY FLOW VISUALIZATION INSIDE A CHANNEL WITH WALL SQUARE PROTUBERANCES IN MODERATE REYNOLDS NUMBERS - Bassan, Rodrigo A. y; Almeida, Odenir de; Mansur, Sergio Said [UNESP]; Vieira, Edson Del Rio [UNESP]; SilvaGomes, J. F.; Vaz, MAP (Inegi-inst Engenharia Mecanica E Gestao Industrial, 2012)
Digital images concerning with the flow inside a channel with wall square protuberances are captured in the present work. Liquid dye injected by means of long hypodermic injection needles has been utilized to make the flow visible. Digital photos and videos have been captured, showing the features of the steady and unsteady flow in such a geometry. All tests have been performed in a low turbulence vertical hydrodynamic tunnel operating in blow-down mode at Reynolds number up to 1000. The characteristic dimension (D) used for calculating Reynolds has been taken as the height of the square protuberances, i.e. equal to 10 mm. The channel has 146 x 30 mm of cross section and square protuberances are orthogonally positioned relatively to the flow, resulting in a blockage ratio of 1/3. Flow instabilities like detachments, recirculation, and vortex shedding have been identified and explained in detail.